Comparing Iconic Memory in Children with and without Attention Deficit Hyperactivity Disorder. - Nastaran Ahmadi; Mohammad Ali Goodarzi; Habib Hadianfard; Norolah Mohamadi; Daryush Farid; Golrasteh Kholasehzadeh; Mohammad Nadi Sakhvidi; Camellia Hemyari (Iranian Journal of Psychiatry, 2013)
Objective: Children with attention deficit hyperactivity disorder (ADHD) do not process most information due to inattention and loss of the opportunity to save and retrieve information. Therefore, these children experience memory impairment. Although visual memory has been previously studied in children with ADHD, iconic memory in these children has been less evaluated. We aimed to study the possibility of iconic memory impairment in children with ADHD, and compare the results with that of children without ADHD. Methods: The experimental group of this study were 6-9 year-old children who referred to the Imam Hosein Clinic and were diagnosed as having ADHD by a psychiatrist during 2011-2012 (n=30).The subjects were interviewed clinically by a psychologist; and in order to diagnose ADHD, their parents and teachers were asked to complete the child symptom inventory-4 (CSI-4). The comparison group were 6-9 year-old children without ADHD who studied in 1st and 2nd educational district of Yazd (n=30). Subjects’ ico ic memory was assessed using an iconic memory task. Repeated measure ANOVA was used for data analysis. Results: Based on the iconic memory test, the mean score of ADHD children was significantly lower than that of children without ADHD (P